The Role of Madrasah Principal in Maintaining the Existence of Madrasah Diniyyah Takmiliyah in Tamban Catur District - Nurul Hikmah; Cindy Marcelinna Putri; Muhammad Redha Anshari (Al-Fahim)
Madrasah Diniyah Takmiliyah Awwaliyah as a non-formal Islamic educational institution has an important role in the progress of the Islamic ummah in Indonesia. However, currently, many Islamic madrasahs are no longer active for various reasons. This is due to several things, including curriculum, finances, infrastructure, and lack of cooperation between Islamic schools and the community. To ensure that the Islamic madrasa can continue to be active and exist, all elements in the madrasa need to play a good role, including the head of the madrasa. The purpose of this research is to examine the role of the head of Madrasah Diniyah Takmiliyah Awwaliyah Thoriqossadah, Tamban Catur District so that the madrasah he leads can continue to exist today. This research is qualitative research located in MDTA Thoriqossadah, Tamban Catur District. The subject of this research is the head of the madrasah. The research results show that the madrasa head has carried out his role well as a decision-maker, information provider, supervisor, and as relationship builder. The role of the madrasah head as a decision maker can be seen in making decisions about using the yellow book-based curriculum, decision making in financial management, it can be seen that financial management is completely carried out by the madrasah starting from planning, extracting sources of funds to reporting, decision making in managing students can be seen from the division of groups classes according to age and ability in reading and writing the Al-Quran. The role of the madrasa head as a relationship builder can be seen from how the madrasa head has good relations with the parents of the students and the government through the head of the Kapuas district's educational boarding school.